Multilevel DC Link Inverter with Reduced Number of Switches and Batteries - Y. R. Manjunatha; Anand B A (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
Multilevel inverters are the best solution for medium and high voltage power electronic drives. Because of its unique characteristic of synthesizing sinusoidal voltage with less harmonic contents using several DC sources. In a three phase multilevel inverter, each phase of a cascaded H-bridge inverter requires ‘n’ DC sources to obtain 2n + 1 output voltage levels. One particular disadvantage  is that,  it  increases  number  of power semiconductor switches. To overcome this disadvantage a multilevel  DC  link  inverter (MLDCLI) with reduced number of switches and batteries is proposed.DOI: http://dx.doi.org/10.11591/ijpeds.v4i3.4618